Developing a learning platform for AVT: challenges and solutions - Paula Igareda; Anna Matamala (JoSTrans: The Journal of Specialised Translation)
The implementation of the Bologna process across Europe has meant a shift in university teaching methodology and practice. While the focus was previously on lectures, the new system proposes more active methodologies, with an emphasis on new technologies. This new paradigm has created the need to offer new learning environments. This is primary the aim of AVT-Lp (Audiovisual Translation Learning Platform), a software system developed at the Universitat Autònoma de Barcelona (UAB) to foster autonomous audiovisual translation learning. This article presents this platform and discusses the main challenges that were faced and overcome during its development. These difficulties were experienced at three different phases of the project: while devising the initial platform design, while developing the platform, and during system testing.